2001
DOI: 10.1007/s002800100375
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-induced apoptosis in caspase-8-deficient neuroblastoma cells is mediated through direct action on mitochondria

Abstract: These results indicate that the p53/Fas/caspase-8 system does not play a role in mediating the apoptotic action of doxorubicin in the human neuroblastoma cell line SKN-SH. Thus, mitochondria and downstream apoptotic signaling intermediates may be considered as key targets for doxorubicin-induced apoptosis in neuroblastoma tumors having deficiencies in the Fas/caspase-8 system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…Its main activity is related to the inhibition of topoisomerase II, free radical formation and oxidative DNA damage (2,3). It is believed that DOX induces apoptosis through cytochrome c release and activation of caspase-3 (4,5). However, in our previous study we observed the occurrence of cells not only with apoptotic features, but those characteristic of mitotic catastrophe (6).…”
Section: Introductionmentioning
confidence: 77%
“…Its main activity is related to the inhibition of topoisomerase II, free radical formation and oxidative DNA damage (2,3). It is believed that DOX induces apoptosis through cytochrome c release and activation of caspase-3 (4,5). However, in our previous study we observed the occurrence of cells not only with apoptotic features, but those characteristic of mitotic catastrophe (6).…”
Section: Introductionmentioning
confidence: 77%
“…Unfortunately, despite its potent antitumor effects, DOXO is not a safe drug and its use is associated with unwanted side effects, especially a cardiac toxicity which is common to most anthracycline derivatives (Zucchi and Danesi, 2003). DOXO induces mitochondria-dependent apoptosis in heart and cardiomyocytes (Arola et al, 2000;Rebbaa et al, 2001;Green and Leeuwenburgh, 2002) and it is assumed that cardiomyocytes apoptosis is responsible, at least in part, for DOXO-induced cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Like LCL-30, doxorubicin is a lipophilic cationic molecule that may compromise mitochondrial integrity (33). There is strong evidence that doxorubicin increases endogenous ceramide levels in cancer cells by either activation of neutral sphingomyelinase and/or induction of the de novo pathway of ceramide metabolism (2, 34 -38).…”
Section: Does the Coadministration Of Doxorubicin Enhance Cell Toxicimentioning
confidence: 99%